THE HOLY PLACE OF OUR PEOPLE – KHOJAIGOR TEMPLE - Foziljon Bobomurodov (American Journals, 2023)
The article talks about the shrine in the Northern Surkhan oasis, in particular, in the village of Taytavo in the Sariosi region.
Keywords: Surkhandarya region, Taytavo village, Khojaigor, pilgrimage, shrine, belt, cave, saint, chillkhana.